1995
DOI: 10.1530/eje.0.1330216
|View full text |Cite
|
Sign up to set email alerts
|

Urinary iodine excretion in Belarus children

Abstract: Casual urine samples were collected to determine iodine excretion of 1680 Belarus children during 1990-1994. The subjects, 8-16 years old, were from nine different regions of Belarus; 60% were from the Gomel oblast, which has been associated with relatively high levels of radioiodine fallout and increased incidence of thyroid cancer. Most of the median values indicate borderline/low iodine intake or mild iodine deficiency. Ranges were wide but 163 children excreted < 20 micrograms I/l urine and they should be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 5 publications
0
5
0
1
Order By: Relevance
“…Of interest, Gomel Oblast, the region with the highest prevalence of post-Chernobyl childhood thyroid cancer, may have had milder iodine deficiency than other regions in Belarus. In the study by Ashizawa et al (7) urinary iodine in Gomel indicated that iodine intake was optimal whereas Mityukova et al (8) and Arinchin et al (9) reported mild iodine deficiency.…”
Section: Iodine Nutrition In Ukraine and Belarusmentioning
confidence: 98%
“…Of interest, Gomel Oblast, the region with the highest prevalence of post-Chernobyl childhood thyroid cancer, may have had milder iodine deficiency than other regions in Belarus. In the study by Ashizawa et al (7) urinary iodine in Gomel indicated that iodine intake was optimal whereas Mityukova et al (8) and Arinchin et al (9) reported mild iodine deficiency.…”
Section: Iodine Nutrition In Ukraine and Belarusmentioning
confidence: 98%
“…Together with Dr. Jason Wynberg of the University of Toronto, we initiated an investigation of children from the affected regions because of a) the presumed higher sensitivity of children to ionizing radiation; b) their high consumption of dairy products; c) the increased prevalence of goiter among residents of these iodine-deficient regions (16)(17)(18); d) the unknown contribution to dose of the short-lived radioisotopes of iodine; and e) the reported increase of thyroid cancer in children living in Belarus, Ukraine, and southern Russia (3)(4)(5).…”
Section: Thyroidmentioning
confidence: 99%
“…Earlier surveys of iodine excretion and goiter prevalence in the Chornobyl region beginning 5 years after the accident also found the affected areas of Ukraine to be more iodine deficient than Belarus (9)(10)(11). In a 1991 study of diffuse goiter diagnosed using ultrasonography-based thyroid volumes (10), rates in the Kyiv (54%) and Zhytomyr (38%) regions of Ukraine were more than double those in the Gomel (18%) and Mogilev (22%) regions of Belarus.…”
mentioning
confidence: 92%